ATTENTION-DEFICIT/HYPERACTIVITY DISORDER (ADHD): NEUROBIOLOGICAL BASES, CLINICAL MANIFESTATIONS, AND EVIDENCE-BASED THERAPEUTIC APPROACHES - do Nascimento, Cláudio José Alves; Alves, Jamila Silva (Seven Editora, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder with early onset, characterized by persistent patterns of inattention, hyperactivity, and/or impulsivity of an intensity inconsistent with the developmental level, producing clinically relevant functional impairment in multiple contexts (family, school, social, and later, occupational). In Brazil, the topic has been given official national guidelines within the scope of the SUS (Unified Health System), through the Clinical Protocol and Therapeutic Guidelines (PCDT) approved by Joint Ordinance of the Ministry of Health, which specifies general criteria for diagnosis, monitoring, and organization of care within the network. DOI: https://doi.org/10.56238/sevened2026.001-007